Induksi kalus Artemisia vulgaris L. dengan Pemberian Beberapa Konsentrasi 2,4-Dichlorophenoxyacetic Acid(2,4-D) - Nazhira - Fadhilah; Zozy Aneloi Noli; Suwirmen - Suwirmen (Universitas Andalas, 2015)
The research about callus induction Artemisia vulgaris L. by giving several concentration 2,4-Dichlorophenoxyacetic acid (2,4-D), has been done from May to August 2015 in Plant Physiology Laboratory and Tissue Culture, Department of Biology, Faculty of Mathematics and Natural Science, University of Andalas. The aim of this studywas found the effective concentration of 2,4-D to induce callus of A. vulgaris. The research used Completely Randomized Design (CRD) with 7 treatments and 4 replications. The treatments were : without 2,4-D (control); 0.25 mg/L 2,4-D; 0.50 mg/L 2,4-D; 0.75 mg/L 2,4-D; 1.00 mg/L 2,4-D; 1.25 mg/L 2,4-D; 1.5 mg/L 2,4-D. The result showed that 0.25-1,5 mg/L 2,4-D were able induction callus of A. vulgaris, withcompactuntilthefriabletexture, color ofthe resultingcallusisyellowish green, brownish-green, yellow-brown, whiteyellowishandgreenishwhite. 2,4-D 1.5mg/Lwas the best concentrationto increase fresh weight of callus.